2010
DOI: 10.1007/s11999-009-1113-2
|View full text |Cite
|
Sign up to set email alerts
|

Chest Wall Mass in a 50-year-old Woman

Abstract: A 50-year-old postmenopausal woman presented with a 9-month history of a lump on her left anterior chest wall in the region of the 2nd and 3rd costochondral junction. She reported the mass changed in size and at times felt soft and fluctuant. It intermittently swelled, causing her local discomfort followed by periods of spontaneous regression, which would be accompanied by inflammation localized to the surrounding chest wall. Physical examination revealed a firm mass along the left superior chest wall measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In our patient, an incisional biopsy was not performed as such a biopsy might increase the risk of systemic dissemination in the event of a parasitic cyst. Inflammatory arthritis may manifest as costosternal pain and swelling but show radiographic features like reactive periostitis and hyperostosis [8]. Crystal deposition disorder may present as costosternal pain and swelling and display hyperostosis radiographically.…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…In our patient, an incisional biopsy was not performed as such a biopsy might increase the risk of systemic dissemination in the event of a parasitic cyst. Inflammatory arthritis may manifest as costosternal pain and swelling but show radiographic features like reactive periostitis and hyperostosis [8]. Crystal deposition disorder may present as costosternal pain and swelling and display hyperostosis radiographically.…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…. The younger age group is affected more with smaller bone involvement [3]. Biscaglia et al has found the incidence as 45% among individuals below 20 years of age [4].…”
Section: Case Reportmentioning
confidence: 99%